2016
DOI: 10.1016/j.jds.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Debris extrusion by glide-path establishing endodontic instruments with different geometries

Abstract: Background/purpose Glide-path preparation is an important step during initial endodontic procedure to reduce shaping-instrument fracture. The aim of this study was to evaluate the amount of apically extruded debris produced by glide-path preparation instruments with different geometric designs. Materials and methods Forty teeth extracted for periodontal reasons were randomly divided into four groups ( n = 10). The working length was standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 34 publications
6
37
0
1
Order By: Relevance
“…), greater amounts of apically extruded debris (Ha et al . ), greater incidence of postoperative pain and slower symptom resolution (Pasqualini et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), greater amounts of apically extruded debris (Ha et al . ), greater incidence of postoperative pain and slower symptom resolution (Pasqualini et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The creation of glide path can be affected by the degree of canal curvature, and the experience of the operator (De-Deus et al 2013). In addition, it is also difficult and time-consuming to create a glide path using manual files; they might also cause more canal transportation (Pasqualini et al 2012a), less centred canal preparations (Alovisi et al 2017), greater amounts of apically extruded debris (Ha et al 2016), greater incidence of postoperative pain and slower symptom resolution (Pasqualini et al 2012b). For this reason, the creation of glide paths using rotary NiTi files is recommended for achieving more predictable results, especially in curved canals (Alovisi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when compared to the reciprocal systems, the rotary systems have the advantage of the decrease in postoperative complications by enabling the removal of lower amount of debris from the apical. 25 In previous studies 18,26 reported that the ProGlider had the least extrusion of debris among the other rotary NiTi instrument groups. They analysed the geometric differences resulted in the difference of debris extrusion.…”
Section: Discussionmentioning
confidence: 97%
“…Previous laboratory studies have reported that manual glide path preparation may extrude greater amounts of debris and bacteria compared to mechanical glide path preparation using NiTi instruments (Ha et al . , Dagna et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study are in accordance with the findings of Pasqualini et al (2012) regarding the lower incidence of postoperative pain after glide path preparation with NiTi rotary instruments, since glide path preparation using both reciprocating and rotating NiTi instruments led to significantly less postoperative pain incidence than in the manual group. Previous laboratory studies have reported that manual glide path preparation may extrude greater amounts of debris and bacteria compared to mechanical glide path preparation using NiTi instruments (Ha et al 2016, Dagna et al 2017. A linear filing motion creates a greater amount of debris than rotational instrumentation techniques (Al-Omari & Dummer 1995).…”
Section: Discussionmentioning
confidence: 99%